2000
DOI: 10.1258/0022215001904554
|View full text |Cite
|
Sign up to set email alerts
|

Superficial parotidectomy under local anaesthesia

Abstract: We report a case of superficial parotidectomy performed under local anaesthesia. The patient presented with a parotid lump in which aspiration cytology showed cells consistent with mucoepidermoid carcinoma or adenocarcinoma ex pleomorphic adenoma. Despite counselling the patient refused general anaesthesia but accepted the need for removal of the pathology. We have been unable to find a single case report in the English literature since 1966 outlying this procedure being undertaken solely under local anaesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In 1996, Sethna et al reported on a technique involving the application of local anesthesia for patients who were candidates for parotidectomy. Later in 2000, Reece et al reported a case of superficial parotidectomy performed while the patient was under local anesthesia, because the patient did not consent to general anesthesia, and achieved good results. Shahid et al reported 3 patients (involving 2 superficial and 1 total parotidectomy) in 2007 who underwent operations while under local anesthesia without complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1996, Sethna et al reported on a technique involving the application of local anesthesia for patients who were candidates for parotidectomy. Later in 2000, Reece et al reported a case of superficial parotidectomy performed while the patient was under local anesthesia, because the patient did not consent to general anesthesia, and achieved good results. Shahid et al reported 3 patients (involving 2 superficial and 1 total parotidectomy) in 2007 who underwent operations while under local anesthesia without complications.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of partial parotidectomy for the treatment of most benign tumors located at the parotid tail, the extracapsular resection of tumors without the need for complete dissection of the facial nerve has become possible, and the use of general anesthesia might not be necessary for this surgical procedure. Some previous experiences have been reported in the literature regarding the possibility of performing parotidectomy while the patient is under sedation with local anesthesia as an alternative for patients with shorter procedures and those with comorbidities that are associated with increased anesthetic risk …”
Section: Introductionmentioning
confidence: 99%
“…The first report of parotid surgery under local anesthesia came from Japan in 1987, which was a lumpectomy performed for adenocarcinoma [2]. The first report of a formal superficial parotidectomy under local anesthesia was reported by a British group in 2000, for a pleomorphic adenoma in a patient that was otherwise healthy but refused general anesthesia [3]. Several international series have followed, with variations in indications and technique.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of malignancy, surgical excision is key to achieving better locoregional control, disease-free survival, and overall survival compared to nonsurgical treatments such as radiation [1]. Parotidectomy under local anesthesia is a treatment option that has been reported in other countries for a wide variety of indications [2][3][4][5][6][7][8][9]. We report our series of six patients undergoing parotidectomy under local anesthesia, which is the largest series reported in the United States to date.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few reports of parotid surgeries under local anesthesia [5][6][7] using different techniques [5][6][7] with the use of a mixture of bupivacaine and lidocaine for local anesthesia [8].…”
Section: Discussionmentioning
confidence: 99%